2021
DOI: 10.3892/ol.2021.12664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MLL5 and HOXA regulated by NRP1 on radioresistance in A549

Abstract: Radiotherapy is widely used in the management of lung cancer, and physicians are aware that the effect of radiotherapy is dependent on radiosensitivity. Although a series of blockers and activators targeting molecules related to radioresistance have been developed as radiation sensitizers, compensatory mechanisms or drug resistance limits their clinical efficacy. The identification of a key molecule related to lung cancer cell radioresistance or an effective molecular target is a challenging but important prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…HOXA6 encodes a transcription factor that regulates gene expression and cell differentiation. HOXA6 has been identified to play an important role in cell proliferation, differentiation and invasion, and it has been reported that HOXA6 might be radiation‑sensitive [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HOXA6 encodes a transcription factor that regulates gene expression and cell differentiation. HOXA6 has been identified to play an important role in cell proliferation, differentiation and invasion, and it has been reported that HOXA6 might be radiation‑sensitive [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in colorectal cancer, HOXA6 overexpression has been confirmed by Lin et al ., who have clarified that HOXA6 ablation abrogates the migration and invasion capacity of colorectal cancer cells [ 18 ]. Furthermore, Shao et al have elucidated that HOXA6 can regulate radiation resistance in A549 cells in lung cancer [ 22 ]. In light of previous findings, the research further illustrated that HOXA6 was high-expressed in NPC cells, and the deletion of HOXA6 could inhibit the growth of radiation-resistant NPC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation-resistant cellular models of lung adenocarcinoma show increased NRP1 expression, and the NRP1 inhibitor EG00229 reduces the expression levels and binding capacity of NRP1 [78]. NRP1 regulation of radioresistance in lung cancer involves downstream homeobox genes HOXA6 and HOXA9 [79], and microRNA-9 is able to restore radio-sensitivity in radioresistant lung cancer cells by targeting NRP1 [80]. NRP1 can also promote resistance to molecularly targeted therapies in cancer.…”
Section: Nrp1 Regulation Of Resistance To Anticancer Therapiesmentioning
confidence: 99%
“…Previous studies have supported the notion that elevated NRP1 expression in tumors correlates with poor outcomes. On the other hand, NRP1 is associated with radiation resistance [ 19 ]. However, the molecular mechanism through which NRP1 plays a crucial role in the formation of radiation resistance in lung cancer cells is unknown; in particular, more research into transcription factor regulatory mechanisms is needed.…”
Section: Introductionmentioning
confidence: 99%